Factors affecting agricultural characteristics of Camelina sativa (L.) Crantz under dry-summer subtropical and warm temperate climates - Başalma, Dilek; Gürsoy, Mehtap; Nofouzi, Farzad (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2018)
Camelina sativa is one of the alternative plants that can be used to meetexponential growing vegetable oil deficit in Turkey. The purpose of this studywas to establish factors affecting crop yield and yield components of the C. sativa using eight genotypes at Ankara (Csa type of climate) and Haymana location (Csb type of climate), Turkey which were separated by a distance of 110 km during 2014. The results of the study showed a significant interaction between C. sativa genotypes and locations for all studied variables. The maximum length of plants was established as 60.95 cm using the line Number 402; the maximum seed yield was determined as 1549.0 kg·ha-1 using the CS-CR1670 population; and the maximum crude oil percentage was established as 51.25% using the CR-476/65 population at Ankara location. Whereas, at the Haymana location, the maximum plant height of 56.57 cm was noted using the CS-CR1676 population; the maximum seed yield was determined as 1481.0 kg·ha-1 using the CS-163-2073-72 population; and the maximum crude oil percentage was established as 51.42% using the CS-163-2073-72 population in terms of plant height, seed yield and crude oil percentage: CR-476/65, CS-163-2073-72, CS-CR1670 and CSCR1676, Giessen No.3 and NE2006-1 were the best genotypes. Comparing the two locations, maximum seed yield was noted at Ankara location. It was concluded that both locations with Csa and Csb types of climates were appropriate climates for the cultivation of C. sativa under Anatolian conditions.